Simulation of forward current-voltage characteristics for Schottky diodes with MOS trenches - J. A. Solovjov (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
Present work is devoted to the development of a mathematical model for the forward current-voltage characteristic of Schottky diodes with a metal – oxide – semiconductor (MOS) trench structure, which takes into account the accumulation of the main carriers in silicon near the walls of the trenches at a forward bias. The proposed model considers the decrease of the series resistance of the Schottky diode drift region with an increase in the voltage at the rectifying contact due to the enrichment of silicon with electrons near the walls of the trenches. The proposed model is compared with the experimental results for Schottky diodes with a metal – oxide – semiconductor trench structure with a nominal reverse voltage of 45.0 V and a nominal forward current of 50.0 A. It is shown that the error in calculating the direct voltage value for the new model does not exceed 1.2 % in the range of direct currents from 20.0 to 50.0 A, which is 4.6–9.7 times less than the calculation error for the classical model. The results obtained can be used to develop the structure and geometry of Schottky diodes with a metal – oxide – semiconductor trench structure with required electrical parameters.